Insights into Professional Standards of Informing: Media Legislation and Protection of EU Values in Republic of North Macedonia - Dzamtoska Zdravkovska, Suzana; Andon Majhosev,; Robert Arthur, (Technium Social Sciences Journal, 2020)
At no time before has the focus on the role of the media and its impact on political decision making and social construction been more necessary than during this era of ‘fake news’. Competent, thoughtful, verifiable, and unbiased news reporting is the hallmark of a well-functioning news media. This paper describes the necessary and fundamental requirements for professional journalism as well as the legal obligations to guarantee a proficient media. Using EU regulations and those of the Republic of North Macedonia, the authors illustrate the importance of media regulation to assure that the rights of individuals, social, political, and religious groups are protected from the abuses that can result from unprofessional journalistic practices. Furthermore, the authors also stress the importance of media regulations to safeguard minors from content that could considered abusive and/or detrimental to their development.